Avaliação de microrganismos patogênicos em aerossóis gerados em diferentes processos de tratamento de esgoto - Carolina Larissa Machado (2022)
Wastewater contains several pathogenic microorganisms and, during the different treatment stages, the formation of aerosols may occur, constituting a potential source of dissemination of these pathogens. Therefore, an analysis of the pathogens in aerosols generated at Wastewater Treatment Plants (WWTP) becomes necessary to assess the risk they represent to workers in these environments. The methodology for aerosol sampling at WWTPs is not yet standardized and, in this experimental work, different sampling equipment was used. Aerosol samples were collected through filtration, for approximately 5 days, at two large WWTPs: the first WWTP has wastewater treatment by UASB (Upflow Anaerobic Sludge Blanket) and trickling filter and the other, by conventional activated sludge system. The presence of SARS-CoV-2 in aerosols was analyzed by RT-qPCR and the concentration of four other pathogenic microorganisms in aerosols was analyzed by qPCR: adenovirus, Haemophilus influenzae, Pseudomonas aeruginosa and Staphylococcus aureus. SARS-CoV-2 was not detected in any aerosol samples. All other pathogens analyzed were detected in at least one aerosol sample: adenovirus (11 out of 69), Haemophilus influenzae (1 out of 31), Pseudomonas aeruginosa (10 out of 69) and Staphylococcus aureus (6 out of 69). It is noteworthy that H. influenzae, for the first time, to the best of our knowledge, was quantified in aerosols and return sludge. A risk assessment for adenovirus infection by inhalation was performed based on Quantitative Microbial Risk Assessment (QMRA) methodology and it was concluded that the potential risk is greater than proposed as tolerable in the existing literature. Although there is no information on the viability of the pathogenic organisms detected, the use of personal protective equipment (PPE) should be reinforced to increase the safety of workers. This work was the first, as far as is known, to analyze pathogenic microorganisms in WWTP aerosols in Brazil and presents results that can help the development of future work.